Bacterial cellulose/attapulgite magnetic composites as an efficient adsorbent for heavy metal ions and dye treatment. (1st February 2020) - Chen, Xiao; Cui, Jian; Xu, Xuran; Sun, Bianjing; Zhang, Lei; Dong, Wei; Chen, Chuntao; Sun, Dongping
Graphical abstract: Highlights: Bacterial cellulose (BC) was oxidized and blended with magnetic attapulgite. The adsorption toward Cu 2+ and Cr 6+ is preferential to that of Pb 2+ and reached equilibrium very fast in 60 min. Magnetic ATP@(BCNs/CS) presented much larger adsorption capacity for Cr(VI) and congo red. The adsorption capacity decreased less than 8% after five adsorption-desorption cycles. Abstract: In recent decades, increased industrial activities have led to the release of various pollutants, such as toxic heavy metals, inorganic anions, and organics. It is imperative but challenging to develop an eco-friendly treatment technology with easy operation, low cost, and high efficiency. Here, we describe a design of magnetic purifier, which has biomass-based structure by blending attapulgite/chitosan (ATP/CS) composite with bacterial cellulose nanofibrils (BCNs). Compared to similar materials reported previously, our product exhibited efficient adsorption capacities towards various metal ions including Pb 2+, Cu 2+, and Cr 6+, and anionic organic dyes including Congo red. The adsorption process could be well fitted by Langmuir isotherm and pseudo-second order equation. Additionally, the adsorption capacity only decreased less than 8% after five adsorption-desorption cycles. We expect our design will inspire more efforts to build a multifunctional water purifier with simple operation, and hopefully effectively remove pollutants from wastewater in future practical applications.